New room temperature coacervation scheme for lead traces determination by solid surface fluorescence. Application to wines produced in Argentina - Talio, María Carolina (2015)
Lead traces were preconcentrated on paper filter discs using the coacervation phenomenon based on cationic and anionic surfactant reaction at room temperature. The increase in fluorescent signal of Rhodamine B dye was used for metal quantification by solid surface fluorescence. Experimental variables that influence on preconcentration step and fluorimetric sensitivity were optimized using uni-varied assays. The calibration graph using zeroth order regression was linear from 1.24 × 10− 3 μg L− 1 to 1.25 μg L− 1 with a correlation coefficient of 0.997. At the experimental optimal conditions, a limit of detection of 3.73 × 10− 4 μg L− 1 and a limit of quantification of 1.24 × 10− 3 μg L− 1 were obtained. The method showed good sensitivity, adequate selectivity with good tolerance to foreign ions, and was applied to the determination of trace amounts of Pb(II) in red and white wines produced in Argentina with satisfactory results validated by ICP-MS. The proposed method represents an innovative application of paper filters to solid surface fluorescence methodology.